Potential cyanide poisoning reported to the UK national poisons information service: 2008–2019. (2nd September 2022) - Haden, Mark; Wheatley, Nicola; Gray, Laurence A.; Bradberry, Sally M.; Sandilands, Euan A.; Thanacoody, Ruben H.; Coulson, James
Abstract: Introduction: Cyanide is a prevalent, lethal chemical. Possible sources of exposure include products of combustion, plant material, industry, chemical warfare and terrorism. Methods: Retrospective review of UK Poisons Information Database of telephone enquiries to the National Poisons Information Service between 1 st January 2008 and 31 st December 2019 where cyanide poisoning was considered a possibility. Data extracted included demographics, exposure source, clinical features, Poisoning Severity Score, lactate concentration and antidotes given. Results: A total of 1, 252 cases of suspected cyanide poisoning were identified, 239 (19%) involved children under 10 years. The commonest sources of exposure were ingestion of plant material (437 cases; 35%) and smoke inhalation (399; 32%). Smoke inhalation caused the majority of severe and fatal cases (139; 71%). Clinical features associated with fatal outcomes were cardiac arrest (OR 36.4; 95% CI 14.4–92.2), hypotension (15.8; 7.0–35.9), coma (10.8; 5.6–21.0) and lactic acidosis (7.8; 4.1–14.8). 110 patients (9%) were given an antidote and 40 patients (3%) died. Lactate concentrations correlate with Poisoning Severity Score category ( r = 0.6, p < 0.0001). Serum lactate <2.0 mmol/L was associated with Poisoning Severity Score None or Minor (sensitivity 76%; specificity 86%) and >11.0 mmol/L was associated with fatal outcome (sensitivity 74%; specificity 80%). 61 cases (5%) had severe carboxyhaemoglobin toxicity (COHb >30%). This was associated with a fatal outcome (OR 7.0; 95% CI 1.5-33.7) and there was positive correlation between carboxyhaemoglobin and Poisoning Severity Score, r = 0.57, p < 0.0001. Conclusions: Most cases of ingestion of plant material involved children under five years and resulted in no or mild symptoms. In adults smoke inhalation was associated with the most severe poisoning. The lactate cut-off values associated with each severity score calculated in this study are lower than the values used by NPIS on TOXBASE. Analytical conformation of cyanide exposure was unavailable in the majority of case, limiting the strength of these conclusions.